Professional, organizational and policy-level barriers and facilitators to perinatal mental health care in the United Arab Emirates: A qualitative study - Rouwida ElKhalil; Preetha Menon; Hiba Adam; Rasha Bayoumi; Eny Qurniyawati; Emad Masuadi; Luai A. Ahmed; Rami H. Al-Rifai; Iffat Elbarazi (PLoS ONE, 2026)
Background Perinatal mental health (PMH) is a critical component of maternal and child health, yet significant gaps persist in its integration into routine maternity care in the United Arab Emirates (UAE). Frontline healthcare professionals (HCPs) are central to identifying and addressing PMH concerns; however, their effectiveness is often hampered by multi-level barriers. This qualitative study aimed to identify the professional, organizational, and political-level barriers and facilitators influencing the implementation of PMH care from the perspective of HCPs in the UAE. Methods and findings A descriptive qualitative design was employed. 43 HCPs, including lactation consultants, midwives, maternity nurses, obstetricians, family physicians, paediatricians, and psychiatrists/psychologists, were recruited using purposeful sampling. Data were collected through semi-structured interviews and focus group discussions. Thematic analysis was employed, and barriers and facilitators were categorized to identify key themes. The study identified 31 barriers and 33 facilitators across three ecological levels. Major barriers included PMH awareness and training gaps, low self-efficacy, role-based avoidance, fragmented services, staffing shortages, unclear protocols, and limited insurance coverage. Key facilitators encompassed professional development initiatives, core provider qualities like empathy and advocacy, interprofessional collaboration, integrated care models, supportive organizational policies, and government-led training programs. A critical finding was the role of the multicultural healthcare workforce as a significant facilitator for providing culturally competent care. Conclusion The study identified multi-level barriers and facilitators that shape PMH care delivery in the UAE. Addressing these factors requires a systemic approach, including standardized PMH training, integrated care pathways, clear protocols, and policy reforms for insurance coverage. Leveraging the strengths of the multicultural workforce is essential for developing effective, culturally sensitive PMH services. These findings can guide the development of strategies to support HCPs and improve mental health outcomes for mothers and families.